2021
DOI: 10.32404/rean.v8i1.5698
|View full text |Cite
|
Sign up to set email alerts
|

Production of Ornamental Pyramid Pepper With Reflective Material on Benches in Different Environments

Abstract: Pepper trees have great ornamental value due to the varied colors of their fruits. Thus, the objective was to evaluate the Pyramid cultivar's production in different cultivation environments using benches with reflective material. The experiment was carried out in two protected environments: a) agricultural greenhouse with 42-50% shade screen under the plastic film and b) agricultural screen with black monofilament screen with 18% shade. Inside the environments, the production system was tested with and withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…In hot climate regions, such as the one in the present study, the temperature inside the protected environment is strongly related to the precipitation of the period, and the greater and better distributed over time, the more similar the monthly averages of internal and external temperatures (Silva et al 2021b) as verified in the present study. In winter, the average monthly temperatures also tend to balance the internal and external environments (Paula et al 2017).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In hot climate regions, such as the one in the present study, the temperature inside the protected environment is strongly related to the precipitation of the period, and the greater and better distributed over time, the more similar the monthly averages of internal and external temperatures (Silva et al 2021b) as verified in the present study. In winter, the average monthly temperatures also tend to balance the internal and external environments (Paula et al 2017).…”
Section: Discussionsupporting
confidence: 82%
“…Both the Dickson quality index (Figure 4B) and dry matter of the Handroanthus impetiginosus seedlings (Figures 3B and 4A) were not influenced by the application of silicon, and the best seedlings were formed in full sun. With a significance level of 10%that is, with a 90% probability of occurrence-it was observed that silicon could minimize the severity of production environments, with significant differences, are related to the type of plastic covering film associated or not with the shading screen, as well as the individual use of the shading screen in coverage (Paula et al 2017;Silva et al 2021a;Silva et al 2021b).…”
Section: Resultsmentioning
confidence: 99%